INFLUENCE OF PRODUCT QUALITY AND PRODUCT DESIGN ON PIXY PRODUCT PURCHASE DECISION - Benhart Nainggolan (JOEL: Journal of Educational and Language Research, 2022)
This study aims to determine and analyze how much influence product quality and product design have on Pixy's product purchasing decisions. The analytical method used is the method of multiple linear regression (multi linear regression). The results of the t-test (partial) can be seen that there is an influence between Product Quality Variables on Pixy Product purchasing decisions with a tcount of 3.084 With = 5%, ttable (5%; 51-2 = 49) obtained a ttable value of 1.676 from the description it can be seen that tcount (3.084) > ttable (1.676), as well as the significance value of 0.000 > 0.05, it can be concluded that the first hypothesis is accepted, meaning that product quality (X1) has an effect on purchasing decisions (Y). Testing Hypothesis 2 states that: The results of the t-test (partial) can be seen that there is an influence between Product Design on the Pixy Product Purchase Decision with a tcount of -0.271 With = 5%, ttable (5%; 51-2 = 49) obtained the value ttable of 1.676 from the description it can be seen that tcount (-0.271) < ttable (1.676), and the significance value is 0.788 <0.05, it can be concluded that the second hypothesis is rejected, meaning that Product Design (X2) has no effect on Purchase Decisions (Y) . Testing Hypothesis 3 states that: Product Quality and Product Design have a joint effect on the Pixy Product Purchase Decision (Case Study on STIE Bina Karya Tebing Tinggi Students). This is evident from the results of the F test which obtained an Fcount of 8,119 With = 5%, dk of numerator: 3, dk of denominator: 51-2-1(5%; 2; 48; ftable 3,191) obtained ftable value of 3.191. From this description, it can be seen that Fcount (8.119) > Ftable (3.191), and a significance value of 0.001 <0.05, it can be concluded that the third hypothesis is accepted, meaning that Product Quality (X1) and Product Design (X2) have a joint effect ( simultaneous) on the Purchase Decision Variable (Y).